2015
DOI: 10.1021/acs.chemrestox.5b00153
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antiproliferative Effects of a New Cucurbitacin B Derivative and Chemotherapy Drugs on Lung Cancer Cell Line A549

Abstract: Nonsmall cell lung cancer (NSCLC) represents an important cause of mortality worldwide due to its aggressiveness and growing resistance to currently available therapy. Cucurbitacins have emerged as novel potential anticancer agents showing strong antiproliferative effects and can be promising candidates for combined treatments with clinically used anticancer agents. This study investigates the synergistic antiproliferative effects of a new semisynthetic derivative of cucurbitacin B (DACE) with three chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 54 publications
0
16
0
1
Order By: Relevance
“…F‐actin and vimentin are also major mediators that regulate the cytoskeletal network tension (Janmey, Euteneuer, Traub, & Schliwa, ; Liu, Lin, Tang, & Wang, ). A previous study reported that CuB caused morphological changes in the cytoskeleton of lung cancer cells by inducing F‐actin polymerization (Marostica et al, ). Our data demonstrate that increasing the CuB treatment concentration, F‐actin aggregates around the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…F‐actin and vimentin are also major mediators that regulate the cytoskeletal network tension (Janmey, Euteneuer, Traub, & Schliwa, ; Liu, Lin, Tang, & Wang, ). A previous study reported that CuB caused morphological changes in the cytoskeleton of lung cancer cells by inducing F‐actin polymerization (Marostica et al, ). Our data demonstrate that increasing the CuB treatment concentration, F‐actin aggregates around the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…CuB is a representative natural compound for anticancer activities. Recently, CuB was reported to enhance the anticancer effects of DDP in lung, ovarian, cutaneous squamous cell carcinoma, and laryngeal squamous cell carcinoma (20,(36)(37)(38). However, the relationship between CuB and DDP-resistance in GC cells has yet to be firmly established.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some drug combinations show strong synergism that helps to achieve the same therapeutic effect with lower dose and, hence, less toxicity [34][35][36][37][38][39][40][41][42]. Some reports have shown that cucurbitacins show a synergistic effect with chemotherapeutic agents that are already established in the treatment of human cancers [38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%